Food preferences and rhythms of feeding activity of two co‐existing demersal fish, the longspine snipefish, Macroramphosus scolopax (Linnaeus, 1758), and the boarfish Capros aper (Linnaeus, 1758), on the Mediterranean deep shelf. (21st April 2015) - Carpentieri, Paolo; Serpetti, Natalia; Colloca, Francesco; Criscoli, Alessandro; Ardizzone, Giandomenico
Abstract: The feeding behaviour of two potentially competing species, the longspine snipefish, Macroramphosus scolopax, and the boarfish Capros aper was examined. While both species are very abundant along the Mediterranean coast and are regularly caught by demersal trawlers, they are of no commercial value. The diets of boarfish and longspine snipefish were investigated from samples collected between January 2001 and May 2002. Variations in the diet with fish size and season, as well as diet overlap and diversity were explored. Mysid shrimps, amphipods and gastropods were the most important food items in the diet of longspine snipefish. During ontogenetic development, M. scolopax occupies different trophic levels: the diet shifts from being predominantly composed of mysids ( Anchialina agilis, Lophogaster typicus, Erythrops sp., Leptomysis spp.) in the smaller longspine snipefish [<6.5 cm total length (TL)] towards decapods ( Anapagurus laevis ) and amphipods ( Leucothoe incisa, Eusirus longipes, Hyperidea) in the larger individuals (>6.5 cm TL). Crustacean decapods and copepods were the most important prey in the stomachs of boarfish. Mysids ( Lo. typicus ), euphausiids and nematodes were present in the larger individuals (>8 cm TL). A more generalist diet, still containing copepods, crustacean decapods, gastropods ( Limacina retroversa ) and a large variety of amphipods ( e.g. Phtysica marina, Stenotoe bosphorana ) and mysids ( e.g. A. agilis, Leptomysis spp., Erythrops sp.), dominated the diet of C. aper between 2 and 8 cm TL. Diet overlap between longspine snipefish and boarfish was very low and the differences in stomach species diversity were explained by season and fish size.